The Role of Summer Leads in Melting Sea Ice - Paulson, Clayton A.; Pegau, W. S. (1998)
The long-term goal of this study is to understand and quantify the processes which control the input of solar energy into summer leads and the disposition of this energy into lateral melting, bottom melting, and heat storage. See also ADM002252. The original document contains color images.